Adaptive inclusive space of a higher education institution — its characteristics, functions and structure - Shemihon, N. (Problems of Engineer-Pedagogical Education, 2020)
The article discusses the functions of the educational space of a higher education institution. It is noted that the educational space is a system that has its structure within which the development of professional and personal qualities of the student takes place, a system that is in a dynamic interaction with the subjects of the educational environment and social space (so that it responds flexibly to the requests of society and participants of the educational process), is exposed to organizational and design influences. It is substantiated that inclusion is a process that means absolute involvement of a person with special needs in the educational space, broadens the understanding of the characteristics, functions and structure of the specified space. The study highlights the following characteristics of an adaptive inclusive space. Dynamics is regarded as the ability to respond to the needs of a student with special needs, and to ensure constant unity of the subjects of the educational process and their relationships. Integrity means ensuring the unity of the target, content and process components. Adaptation of a student with special needs serves as the goal of the adaptive inclusive space and is realized through meaningful activity that is subordinate to the goal. Activity that is subordinated to a specific goal is realized through a process that is a set of sequential actions aimed at achieving the goal of adapting students with disabilities to learning. Personnel-development orientation is about focusing on the individual abilities of students and creating for each of them an individual trajectory of learning with regard to their special needs. The adaptive function of the inclusive educational space is to ensure complete integration of students with special educational needs in the educational process, which is a decisive element in higher education. The inclusive educational space, regarded as a system that is dynamically interacting with the subjects of the educational environment and social space, has its structure consisting of adaptive components that complement the characteristics of an inclusive space and reveal its adaptive functions and opportunities. An undertaken analysis of the components showed their poor implementation in the inclusive educational space of Ukrainian higher education institutions.